Noninvasive Respiratory Support during Pediatric Critical Care Transport: A Retrospective Cohort Study - Hutton, Hayley; Sherif, Ahmed; Ari, Abhijit; Ramnarayan, Padmanabhan; Jones, Andrew (Journal of Pediatric Intensive Care, 2022)
Noninvasive respiratory support (NRS) including high flow nasal cannula (HFNC), continuous positive airway pressure (CPAP), and bilevel positive airway pressure (BiPAP) is increasingly used for children with respiratory failure requiring interhospital transport by pediatric critical care transport (PCCT) teams. In this retrospective observational study of children receiving NRS on transport between January 1st, 2017 and December 31st, 2019 by a single PCCT service in England, we describe a cohort of children, looking at patient characteristics, journey logistics, adverse events, and failure of NRS (as defined by emergency intubation on transport or within 24 hours of arriving on the pediatric intensive care unit), and to attempt to identify risk factors that were associated with NRS failure. A total of 3,504 patients were transported during the study period. Three hundred and seventeen (9%) received NRS. Median age was 4.9 months (IQR: 1.0–18.2); median weight was 5.1 kg (IQR: 3.1–13). The primary diagnostic category was cardiorespiratory in 244/317 (77%) patients. Comorbidities were recorded in 189/317 (59.6%) patients. Median Pediatric Index of Mortality-3 (PIM3) score was 0.024 (IQR: 0.012–0.045). Median stabilization time was 80 minutes while median patient journey time was 40 minutes. Nineteen adverse events were described (clinical deterioration, equipment failure/interface issues) affecting 6% of transports. The incidence of NRS failure was 6.6%. No risk factors associated with NRS failure were identified. We concluded that NRS can be considered safe during pediatric transport for children with a wide range of diagnoses and varying clinical severity, with a low rate of adverse events and need for intubation on transport or on the PICU.
Keywords: noninvasive ventilation; high flow nasal cannula; transport; critical care; infant; child